3D Wayang Kulit: traditional shadow puppetry meets modern display technology. (2016) - Parikesit, Gea Oswah Fatah
Displaying shadows stereoscopically in three dimensions may help to preserve the art of Wayang Kulit, i.e. the UNESCO-listed traditional shadow puppetry originated in Indonesia. This paper presents the optical engineering of stereoscopic shadows as applicable for a Wayang Kulit performance. Using a set of governing equations that is developed using the geometrical optics of shadows, we perform numerical analysis on how various parameters can influence the stereoscopic shadows. Experimental demonstration of the method is described using a model setup of Wayang Kulit. Our results may provide useful technical guidelines not only for Wayang Kulit puppeteers but also for all shadow puppeteers in general who desire to use stereoscopic three-dimensional display in their performances.